2018
DOI: 10.3389/fnhum.2018.00356
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Transcranial Magnetic Stimulation on DLPFC Changes Resting State Networks and Cognitive Function in Patients With Bipolar Depression

Abstract: Introduction: Bipolar patients have abnormalities in cognitive functions and emotional processing. Two resting state networks (RSNs), the default mode network (DMN) and the sensorimotor network (SMN), play a decisive role in these two functions. Dorsolateral prefrontal cortex (DLPFC) is one of the main areas in the central executive network (CEN), which is linked to the activities of each of the two networks. Studies have found DLPFC abnormalities in both hemispheres of patients with bipolar depression. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 88 publications
1
21
0
Order By: Relevance
“…The changes come from rTMS in brain activity and connectivity can been detected through a variety of techniques such as transcranial magnetic stimulation (TMS), positron emission tomography (PET), near infrared spectroscopy (NIRS) (20), electro-and magnetoencephalography (EEG/MEG) (21), low-resolution electromagnetic tomography (eLORETA) (22), and finally functional magnetic resonance imaging (fMRI) (23). fMRI is rapidly becoming the most popular technique for its value of identifying the abnormalities of cortical activity and connectivity across almost every major neurological and psychiatric disease.…”
Section: Introductionmentioning
confidence: 99%
“…The changes come from rTMS in brain activity and connectivity can been detected through a variety of techniques such as transcranial magnetic stimulation (TMS), positron emission tomography (PET), near infrared spectroscopy (NIRS) (20), electro-and magnetoencephalography (EEG/MEG) (21), low-resolution electromagnetic tomography (eLORETA) (22), and finally functional magnetic resonance imaging (fMRI) (23). fMRI is rapidly becoming the most popular technique for its value of identifying the abnormalities of cortical activity and connectivity across almost every major neurological and psychiatric disease.…”
Section: Introductionmentioning
confidence: 99%
“…A study that incorporated a large BD sample (n = 146) found that "cognitive-affective" (e.g., emotional or cognitive) as opposed to somatic (e.g., bodily related) symptoms of depression predicted a superior response to rTMS with loss of interest being the most significant cognitive-affective symptom influencing treatment response (Rostami, Kazemi, Nitsche, Gholipour, & Salehinejad, 2017 (Kazemi et al, 2018;Myczkowski et al, 2018), executive functioning (Kazemi et al, 2018), working memory (Myczkowski et al, 2018), attention and processing speed (Myczkowski et al, 2018), and inhibitory control (Myczkowski et al, 2018). A study that incorporated a large BD sample (n = 146) found that "cognitive-affective" (e.g., emotional or cognitive) as opposed to somatic (e.g., bodily related) symptoms of depression predicted a superior response to rTMS with loss of interest being the most significant cognitive-affective symptom influencing treatment response (Rostami, Kazemi, Nitsche, Gholipour, & Salehinejad, 2017 (Kazemi et al, 2018;Myczkowski et al, 2018), executive functioning (Kazemi et al, 2018), working memory (Myczkowski et al, 2018), attention and processing speed (Myczkowski et al, 2018), and inhibitory control (Myczkowski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have suggested the potential benefit of TMS (Kazemi et al, 2018;Myczkowski et al, 2018), executive functioning (Kazemi et al, 2018), working memory (Myczkowski et al, 2018), attention and processing speed (Myczkowski et al, 2018), and inhibitory control (Myczkowski et al, 2018). Notably, these few studies incorporated varied TMS protocols (bilateral vs. unilateral) and types of TMS treatment (deep TMS vs. standard rTMS), so it…”
Section: Discussionmentioning
confidence: 99%
“…Weak rTMS-induced electric fields produce neural entrainment in humans Ando et al (2018) RMT 90 n/r 3 Bai et al (2016) RMT 90 n/r 4 Bharath et al 2017RMT 90 n/r 5 Cao et al (2018) RMT 100 44.5 6 Capotosto et al (2017) RMT 100 n/r 7 Cha et al (2018) RMT 110 n/r 8 Chen et al (2017) RMT 110 n/r 9 D'Agata et al 2016RMT 80 n/r 10 Daltrozzo et al (2016) RMT 90 n/r 11 DelFelice et al 2016RMT 100 58.6/61.9 12 DiGiacomo et al 2018RMT 80 47.4 13 Emrich et al 2017RMT 110 72 14 Fisher et al (2018) RMT 90 n/r 15 Gongora et al 2016RMT 80 47.4 16 He et al 2018RMT 100 n/r 17 Hunter et al 2018RMT 80-120 n/r 18 Jin et al 2017RMT 90 n/r 19 Kamp et al (2016) RMT 110 n/r 20 Karton et al (2017) vMT 80 n/r 21 Kazemi et al (2016) RMT 100/120 n/r 22 Kazemi et al (2018) RMT 100/120 n/r 23 Keuper et al (2018) FXD i/r 50 24 Kim et al (2016) vMT 110 n/r 25 Kito et al (2017) MT 120 n/r 26 Koch et al (2018) RMT 110 60. 8 27 Li et al (2016) MT 100 n/r 28 RMT 110 n/r 29 RMT 110 n/r 30 Lowe et al (2018) RMT 80 52/53 31 Lozeron et al (2017) RMT 80 n/r 32 Moebius et al (2017) RMT 110 n/r 33 Nathou et al (2018) RMT 80 n/r 34 Nicolo et al (2016) vMT 90 n/r 35 Noda et al (2017) RMT 95 82.…”
Section: Supplemental Informationmentioning
confidence: 99%